2015
DOI: 10.1002/jgm.2823
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered mesenchymal stromal cells producing TNFα have tumour suppressing effect on human melanoma xenograft

Abstract: The results of the present study demonstrate that tumour cells respond to hTNFα-based treatment mediated by genetically engineered AT-MSC/hTNFα both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Some studies have shown that MSCs suppress tumor progression by inducing apoptosis or arresting cell cycle [18,32,33], whereas others have shown that hMSCs promote tumor progression by suppressing immune responses [34e36], promoting angiogenesis [37e41] and promoting cancer cell proliferation [42e44]. However, it is notable that the studies that showed anti-cancer effects of MSC or MSC with TNF-a used TRAIL-sensitive cancer cell lines, such as A375, SJBR3 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that MSCs suppress tumor progression by inducing apoptosis or arresting cell cycle [18,32,33], whereas others have shown that hMSCs promote tumor progression by suppressing immune responses [34e36], promoting angiogenesis [37e41] and promoting cancer cell proliferation [42e44]. However, it is notable that the studies that showed anti-cancer effects of MSC or MSC with TNF-a used TRAIL-sensitive cancer cell lines, such as A375, SJBR3 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tropism of MSCs has been exploited for the delivery of therapeutic genes in anticancer therapy, and this approach has proven to be successful in different preclinical models of cancer . However, for clinical use, it would be desirable if localization of sufficient MSCs within tumors could be achieved by MSC‐mediated gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To further reinforce the potency of MSCs, they can be expanded and genetically manipulated under standard cell culture conditions, making them an attractive target for cellular gene therapy . Various gene delivery vectors for MSCs, including nonviral systems based on eukaryotic expression plasmids, transposons and artificial chromosomes, as well as viral vectors derived from retro‐, lenti‐, adeno‐, baculo‐ and adeno‐associated viruses, are currently available . Each transfer vector has specific benefits and disadvantages, which have to be carefully evaluated with regard to its particular final application.…”
Section: Introductionmentioning
confidence: 99%